Is it possible to enforce the law without sanctioning?: applying regulation with a “responsive” approach in Peru, with regard the advocacy strategy about the bureaucratic barriers in the market of public utilities - Ochoa Mendoza, Francisco (2016)
Expensive and excessive regulations may affect the number of firms by discouraging them to access and remain into the market. Despite of such a fact, worldwide there are few legal mechanisms within competition law able to control regulatory activity. This document describes briefly the Peruvian mechanism of regulatory oversight through the Indecopi´s Elimination of Bureaucratic Barriers Commission, which has reached in less than 3 years the voluntary elimination of more than 1000 regulatory and  administrative burdens affecting, inter alia, the market of the deployment of infrastructure on public utilities. This has been the result of a strategy that not relies on sanctioning administrative procedures but in a coordinative-oriented approach with the regulatees aiming to reach the effective accomplishment of the law. In turn, the development of such a strategy make possible to show a new style of enforcement in Peru, which has been studied and undertaken in other countries around the world, namely “Responsive Regulation”.